2018
DOI: 10.1155/2018/5131639
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Proximal Radioulnar Synostosis after Closed Reduction for a Radial Neck and Olecranon Fracture

Abstract: Posttraumatic proximal radioulnar synostosis (PPRUS) is a severe complication of radial head and neck fractures known to occur after severe injury or operative fixation. Cases of PPRUS occurring after minimally displaced, nonoperatively treated radial neck injuries are, by contrast, extremely rare. Here, we present a pediatric case of PPRUS that developed after a nonoperatively treated minimally displaced radial neck fracture with concomitant olecranon fracture. While more cases are needed to establish the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some comparative studies have not shown significant differences in the results after closed and open reduction, and this supports the hypothesis that fracture type and initial degree of dislocation are the most important elements for determining functional outcomes [ 25 ]. In contrast, most authors observed a correlation of open reduction with a high rate of complications, such as myositis ossificans [ 26 ], synostosis [ 27 ], and pseudarthrosis [ 7 ]. One of the most feared complications is avascular necrosis of the radial head and nonunion [ 7 , 20 ], and this sometimes requires radial head resection as an ultimate ratio to restore at least a limited pro-/supination.…”
Section: Discussionmentioning
confidence: 99%
“…Some comparative studies have not shown significant differences in the results after closed and open reduction, and this supports the hypothesis that fracture type and initial degree of dislocation are the most important elements for determining functional outcomes [ 25 ]. In contrast, most authors observed a correlation of open reduction with a high rate of complications, such as myositis ossificans [ 26 ], synostosis [ 27 ], and pseudarthrosis [ 7 ]. One of the most feared complications is avascular necrosis of the radial head and nonunion [ 7 , 20 ], and this sometimes requires radial head resection as an ultimate ratio to restore at least a limited pro-/supination.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a direct approach was performed for the ulna. In stage with indomethacin, radiotherapy, and HO resection [13][14][15]23 ; dual therapy with indomethacin and HO resection, 24 and intramedullary nailing. 25 Regardless of what preoperative management is performed, surgical intervention remains the most effective option to restore functional range of motion in patients with limited pronation and supination.…”
Section: Discussionmentioning
confidence: 99%
“…These include the use of adjuvant indomethacin, radiation therapy, and interposition flaps such as adipose tissue, anconeus, or tensor fascia lata. [13][14][15] Some authors have even suggested the combination of all 3 modalities to achieve better results. [16][17][18] The main aim of this study was to report on cases that underwent surgery with a combination of prophylactic triple therapy to confirm that the results are consistently excellent and in keeping with the experiences shared by other centers.…”
mentioning
confidence: 99%
“…Some evidence suggests that increased radial head angulation and/or displacement, as well as associated elbow injuries, may increase the risk of radioulnar synostosis. 30…”
Section: Radioulnar Synostosismentioning
confidence: 99%